Chimeric Antigen Receptor Design and Efficacy in Ovarian Cancer Treatment - Katarzyna M. Terlikowska (International Journal of Molecular Sciences, 2021)
Our increased understanding of tumour biology gained over the last few years has led to the development of targeted molecular therapies, e.g., vascular endothelial growth factor A (VEGF-A) antagonists, poly[ADP-ribose] polymerase 1 (PARP1) inhibitors in hereditary breast and ovarian cancer syndrome (BRCA1 and BRCA2 mutants), increasing survival and improving the quality of life. However, the majority of ovarian cancer (OC) patients still do not have access to targeted molecular therapies that would be capable of controlling their disease, especially resistant or relapsed. Chimeric antigen receptors (CARs) are recombinant receptor constructs located on T lymphocytes or other immune cells that change its specificity and functions. Therefore, in a search for a successful solid tumour therapy using CARs the specific cell surface antigens identification is crucial. Numerous in vitro and in vivo studies, as well as studies on humans, prove that targeting overexpressed molecules, such as mucin 16 (MUC16), annexin 2 (ANXA2), receptor tyrosine-protein kinase erbB-2 (HER2/neu) causes high tumour cells toxicity and decreased tumour burden. CARs are well tolerated, side effects are minimal and they inhibit disease progression. However, as OC is heterogenic in its nature with high mutation diversity and overexpression of different receptors, there is a need to consider an individual approach to treat this type of cancer. In this publication, we would like to present the history and status of therapies involving the CAR T cells in treatment of OC tumours, suggest potential T cell-intrinsic determinants of response and resistance as well as present extrinsic factors impacting the success of this approach.